THE IMPACT OF DESTINATION IMAGE FOR CREATIVE-HUB BUSINESS: CASE STUDY OF BUMI ARSA CREATIVE SPACE - Hadyan Anshari, Rahanandra
The development of tourism destinations over time caused a lot of new forms of destination places. One of them is the creation of a creative hub, a place to enable people for collaborating aimed to bring creative people together. In this thesis, the author brings the example of a creative hub located in the Sukabumi which is Bumi Arsa. Bumi Arsa is a form of government and Penta helix provides the best channel for creative collaboration among the local community. Bumi Arsa presence itself is a key factor in developing business opportunities for the millennials around.